2021
DOI: 10.1038/s41598-021-87896-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of type 2 diabetes mellitus on the corneal endothelium and central corneal thickness

Abstract: Aim of this study is to evaluate the differences in corneal endothelial cell morphology and corneal thickness in patients with and without type 2 diabetes related to age, disease duration, and HbA1c percentage. This retrospective cross-sectional study included 511 (1022 eyes) type 2 diabetes patients and 900 (1799 eyes) non-diabetic patients. The endothelial cell density (ECD), variation in endothelial cell size (CV), percentage of hexagonal cells, and central corneal thickness (CCT) were analyzed using a nonc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 33 publications
(7 reference statements)
2
24
3
Order By: Relevance
“…They found that among all age groups, the subjects with T2DM had shown significantly lower endothelial cell density (ECD), hexagonality, higher CV, and thicker CCT compared to non-diabetic. This difference was more noticeable among long duration DM (more than ten years) patients & higher HbA1c (more than equal to seven percent) [33,34]. When stratified by age criteria, from 60 years groups, corneal endothelial cell findings had shown significantly alteration among DM and controls.…”
Section: Various Studies For Effect Diabetes On Corneamentioning
confidence: 89%
“…They found that among all age groups, the subjects with T2DM had shown significantly lower endothelial cell density (ECD), hexagonality, higher CV, and thicker CCT compared to non-diabetic. This difference was more noticeable among long duration DM (more than ten years) patients & higher HbA1c (more than equal to seven percent) [33,34]. When stratified by age criteria, from 60 years groups, corneal endothelial cell findings had shown significantly alteration among DM and controls.…”
Section: Various Studies For Effect Diabetes On Corneamentioning
confidence: 89%
“…We observed apparent corneal edema and increased corneal thickness in the diabetic mice over the 6 months, which was consistent with the manifestation of corneal thickening and endothelial cell loss of diabetic patients in the clinic. 8 , 32 34 Further, studies have shown that microvascular complications are more common among children with type 2 diabetes at the time of presentation than among those with type 1 diabetes. 35 Mice with type 2 diabetes not only had hyperglycemia but also had increased insulin and glucagon, which may be the reason for greater vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…Storr-Paulsen et al 3 Schultz et al 37 Busted et al 15 Keoleian et al 38 Olsen et al 16 Inoue et al 39 Larsson et al 17 Sudhir et al 40 McNamara et al 14 Ziadi et al 41 Roszkowska et al 18 Sonmez et al 42 Rosenberg et al 19 Wiemer et al 43 Lee et al 20 Beato et al 47 Su et al 21 Wang et al 54 Oriowo et al 22 Xiao et al 55 Modis et al 23 Wang et al 57 Ozdamar et al 24 Calvo-Maroto et al 25 Briggs et al 26 Sanchis-Gimeno et al 27 Altay et al 30 Kumar et al 44 Jeziorny et al 45 Luo et al 46 Ramm et al 48 Çolak et al 49 Hanyuda et al 50 Taşlı et al 51 Srećković et al 52 Suraida et al 53 Deák et al 56 Kim and Kim 58 CCT, central corneal thickness.…”
Section: Increase In Cct Values No Increase In Cct Valuesmentioning
confidence: 99%
“…Larsson et al 17 Storr-Paulsen et al 3 Lee et al 20 Busted et al 15 Calvo-Maroto et al 25 Olsen et al 16 Luo et al 46 Roszkowska et al 18 Srećković et al 52 Rosenberg et al 19 Kim and Kim. 58 Oriowo et al 22 Ozdamar et al 24 Briggs et al 26 Sanchis-Gimeno et al 27 Altay et al 30 Çolak et al 49 Xiao et al 55 conditions in Type-1 DM patients. Blood glucose levels were pharmacologically controlled in these patients.…”
Section: Andmentioning
confidence: 99%
See 1 more Smart Citation